Estratégias competitivas adotadas pelos supermercados de Teresina - Rêgo, Regina Cláudia Ferreira Soares do (2006)
The supermarket retail is facing a great challenge related to the creation of competitive differentials. The entrance of big foreign groups into market, the last years timid economical growing and the decrease of the purchasing power have caused the increase of the competition in this sector. These factors, among others have caused transformations in the supermarket organizations, forcing them to search for modern tools of management, a fundamental necessity to understand their consumers and the reasons that lead them to an establishment to carry out their purchases. In face of it, the identification of the competitive strategies used by the supermarkets in Teresina to overcome the competition was looked for. Twelve supermarkets were chosen for the application of a questionnaire, here it was concluded that important attributes such as the location of the stores are quite used strategies and when well planned they become a differential, associating your tore and your brand with the preference of the consumer.